Creative boot camp booster pack : lieutenant mix - Mumaw, Stefan (New Riders, 2012)
You've completed the Creative Boot Camp training program, surviving 30 days of creativity exercises designed to present fun, engaging opportunities for creative problem solving. Through this practice, you developed skills that you use every day by solving problems with defined purpose and escalating restriction. Now that you've performed those 30 exercises, wouldn't it be great if there were another set of 30 exercises you could complete that would challenge you in the same way? You're in luck. Introducing the Creative Boot Camp Booster Packs. The Creative Boot Camp Booster Packs offer 90 new creative exercises, separated into two collections: The Medium Collection and The General Mix Collection. The Medium Collection offers the 90 exercises segregated by medium: 30 Designer, 30 Writer, and 30 Photographer. The General Mix Collection offers the same 90 exercises in three mixed packs: Brigadier, Major, and Lieutenant. Each mixed Booster Pack contains 10 designer, 10 writer, and 10 photographer exercises. This Booster Pack is the Lieutenant Mix, which means the exercises are a collection of designer, writer, and photographer exercises pulled and mixed from the Designer, Writer, and Photographer Creative Boot Camp Booster Packs, 10 exercises from each. This is a similar format to the Creative Boot Camp Training Program. Each mixed set is different and each provides a well-rounded approach to creative training, challenging you to solve problems using multiple mediums. Solve these problems with relevance and novelty and you'll find the creative boost you are seeking by the conclusion of the pack.